A Study of Northern Indian Economic Life during the Kushana Period: Uncovering the Economic Life of Northern India during the Kushana Period (Journal of Advances and Scholarly Researches in Allied Education, 2018)
A host of scholars have worked on the economic history of India from time to time. A lot of work has been done on the subject but unfortunately scanty attention has been paid to the economic history of India during the Kusana period. Various eminent scholars such as B. N. Mukherjee, B. N. Puri, G. R. Sharma, G. L. Adhya, A. N. Bose, Pran Nath, M. A. Buch, R. N. Saletore, Bhaskar Chatopadhyaya, Kameshwar Prasad, B. R. Mani and many more have dealt with the economic aspects of the Kusana period of Indian history from time to time. Some of them have been too general in their observations while the others have concentrated on only one or two aspects of the economic life of people. Even the works of eminent scholars such as B. N. Mukherjee, B. N. Puri, Bhaskar Chatopadhyaya, and G. R. Sharma etc. more or less deal with the political and social aspects of the Kusana period of Indian history. It has not been possible to work upon each and every minute aspect of the economic life of India during the Kusana period.